Exploring the Mechanism of Pathological Gaming in Adolescents: Focused on the Mediation Paths and Latent Group Comparison - Jeon, Hyeon Gyu; Jeong, Eui Jun; Lee, Sung Je; Kim, Jeong Ae (Frontiers in Psychology, 2022)
Pathological gaming among adolescents has been reported to hamper the achievement of a balanced life and to threaten the development of social competencies. Despite the increasing social concerns on the adolescent users, however, the mechanism of gaming behavior of adolescents has not been sufficiently examined. This study explored the mechanism of pathological gaming among adolescents from three-year longitudinal data of 778 Korean adolescent gamers, by analyzing the effects of negative affects (i.e., anxiety, loneliness, and academic stress) on the degree of pathological gaming through the mediation variables (i.e., aggression and self-control) based on the stimulus-organism-response (S-O-R) framework. Latent class analysis (LCA) was used to uncover potential risk groups, and through partial least squares - structural equation modeling (PLS-SEM) analysis, the mediation pathways to pathological gaming were compared between the risk group and the non-risk group. The results highlighted the key role of academic stress on the degree of pathological gaming. In the entire group, academic stress primarily increased pathological gaming through self-control. The mediation path of self-control was the most influential result in the risk group. Aggression was the key mediator between loneliness and pathological gaming in the non-risk group. The theoretical and practical implications of the results were discussed.